Sintering and Foaming of Barium Silicate Glass Powder Compacts - Agea-Blanco, Boris; Reinsch, Stefan; Müller, Ralf (Frontiers in Materials, 2016)
The manufacture of sintered glasses and glass-ceramics, glass matrix composites and glass-bounded ceramics or pastes is often affected by gas bubble formation. Against this background, we studied sintering and foaming of barium silicate glass powders used as SOFC sealants using different powder milling procedures. Sintering was measured by means of heating microscopy backed up by XPD, DTA, Vacuum Hot Extraction (VHE) and optical and electron microscopy. Foaming increased significantly as milling progressed. For moderately milled glass powders, subsequent storage in air could also promote foaming. Although the powder compacts were uniaxially pressed and sintered in air, the milling atmosphere sig¬ni¬ficantly affected foaming. The strength of this effect increased in the order Ar  N2 < air < CO2. Conformingly, VHE studies revealed that the pores of foamed samples predominantly encapsulated CO2, even for powders milled in Ar and N2. Results of this study thus indicate that foaming is caused by carbonaceous species trapped on the glass powder surface. Foaming could be substantially reduced by milling in water and 10 wt% HCl.